Residual lignin in cellulose nanofibrils enhances the interfacial stabilization of Pickering emulsions. (1st February 2021) - Guo, Shasha; Li, Xia; Kuang, Yishan; Liao, Jianming; Liu, Kai; Li, Jun; Mo, Lihuan; He, Shuaiming; Zhu, Wenyuan; Song, Junlong; Song, Tao; Rojas, Orlando J.
Highlights: Lignocellulosic nanofibrils (LCNF) are prepared from wood using recyclable p -TsOH. The residual lignin content in LCNF can be easily tailored by the hydrolysis temperature. LCNF behavior at the oil-water interface depends on residual lignin concentration. A higher residual lignin in LCNF results in Pickering emulsions with superior properties. Abstract: Lignocellulose nanofibrils (LCNF) were used to prepare oil-in-water Pickering emulsions and to assess the role residual lignin in interfacial stabilization. Two LCNF fractions of similar morphology (length ∼700 nm and width ∼8 nm) and structure (polymorphism and crystallinity) were obtained by microfluidization of fibers obtained by hydrothermal treatment of wood with a recyclable organic acid. The LCNF with higher residual lignin was less hydrophilic and, correspondingly, performed better as Pickering stabilizer, producing emulsions of smaller droplet size and higher resistance to creaming. Long-term emulsion stabilization (over 40 days) was achieved with LCNF at concentrations as low as 0.24 (w/v)% based on emulsion volume. We conclude that LCNF-stabilized Pickering emulsions can be finely tuned by varying the residual lignin content, providing a rationale for LCNF selection according to lignin type and concentration as variables affecting stabilization. Complementary considerations include the possible benefits of the residual lignin in LCNF, including antioxidant and UV absorption properties.